Comparison of radioimmunoassay with the complement fixation test and the indirect haemolysis test in the field diagnosis of bovine brucellosis. - Chappel, R. J. (Cambridge University Press, 1983)
Sera were collected from female cattle in 118 commercial herds being subjected to a programme to eradicate brucellosis by test and slaughter, in an area in which vaccination of heifer calves with Brucella abortus strain 19 was compulsory. Of 4583 sera positive by the Rose Bengal plate test, the brucellosis radioimmunoassay was positive for 1524, the complement fixation test for 1363 and the indirect haemolysis test for 1141. These figures, and supporting evidence from the eradication programme, suggest that the radioimmunoassay may be a useful supplementary test in problem herds.